2015
DOI: 10.1016/j.ophtha.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Corneal High-Order Aberrations and Backscatter in Fuchs' Endothelial Corneal Dystrophy

Abstract: Purpose Suboptimal visual acuity after endothelial keratoplasty has been attributed to increased anterior corneal high-order aberrations (HOAs). In this study, we determined anterior and posterior corneal HOAs over a range of severity of Fuchs endothelial corneal dystrophy (FECD). Design Cross-sectional study. Participants 108 eyes (62 subjects) with a range of severity of FECD and 71 normal eyes (38 subjects). Methods All corneas were examined by using slit-lamp biomicroscopy to determine the severity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 38 publications
3
91
3
1
Order By: Relevance
“…All participants underwent Scheimpflug imaging (Pentacam HR; Oculus, Lynnwood, WA) as described previously. 10 Images were acquired at any time during routine clinic hours (7:30AM to 4:30PM), with 75% of all images acquired before 1:00PM. The "4 Maps Refractive" display of enrolled eyes derived from the instrument's software (Pentacam version 1.21r43) was exported as a high-resolution image, as described previously 1 ; only images meeting the instrument's software quality criteria were included.…”
Section: Scheimpflug Imaging and Tomography Evaluationmentioning
confidence: 99%
“…All participants underwent Scheimpflug imaging (Pentacam HR; Oculus, Lynnwood, WA) as described previously. 10 Images were acquired at any time during routine clinic hours (7:30AM to 4:30PM), with 75% of all images acquired before 1:00PM. The "4 Maps Refractive" display of enrolled eyes derived from the instrument's software (Pentacam version 1.21r43) was exported as a high-resolution image, as described previously 1 ; only images meeting the instrument's software quality criteria were included.…”
Section: Scheimpflug Imaging and Tomography Evaluationmentioning
confidence: 99%
“…4,5 IOL options must be carefully explored when corneal guttae are present. Wacker et al 6 found that anterior corneal HOAs were increased in moderate and advanced Fuchs´ endothelial dystrophy (FED), compared with controls, before clinically visible corneal edema. Likewise, posterior corneal HOAs and corneal backscatter were increased even in mild FED, suggesting that surface aberrations may occur earlier than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…; Wacker et al. ; Zhang & Patel ). Furthermore, the level of HOAs typically found in post‐DSAEK patients sufficed to induce a significant reduction in vision in a study by McLaren & Patel ().…”
Section: Discussionmentioning
confidence: 99%
“…; Wacker et al. ). In the posterior part of the cornea, interface haze between the donor lamella and recipient cornea could affect vision, and graft asymmetry could lead to aberrations from the posterior surface.…”
Section: Introductionmentioning
confidence: 97%